Attitude towards Dance as a Recreational Activity among Undergraduates of University of Ilorin, Nigeria - Bakinde, S. T.; Olaitan, O. Lanrewaju; Ajadi, M. T.; Talabi, A. E.; Adebare, Oyetunji Bashir; Adebayo, T. M. (NIU Journal of Social Sciences; Vol 4 No 1 (2018): KIU Journal of Social Sciences, Vol. 4 No. 1, March 2018, 2018)
This study examined the attitude towards dance as a Recreational activity among undergraduates of university of Ilorin. Six (6) hypotheses were formulated for this study. Descriptive research design was used for the study; data was collected using structured questionnaire and analyzed using descriptive and inferential statistics of percentage and Chi-Square (XÂ²) respectively. All hypotheses were tested at 0.05alpha level. The result revealed that significant difference exists in dance participation of both male and female students in university of Ilorin. The results also revealed that significant difference exists in dance participation of both Christian and Muslim. The researcher recommends that dance activities should be designed in such a way that it will attract studentsâ€™ interest while experts in Human Kinetics should impress on school management to tap into benefits of dance as recreational activity.